PENERAPAN MODEL PEMBELAJARAN COOPERATIVE SCRIPT DALAM MENINGKATKAN PRESTASI BELAJAR SISWA KELAS IV MATA PELAJARAN PAI DI SDN 009 PARIT TERATAT AIR HITAM KECAMATAN SENTAJO RAYA KABUPATEN KUANTAN SINGINGI - Enny Novryda; Bustanur Bustanur; Sopiatun Nahwiyah (Universitas Islam Kuantan Singingi, 2020)
The Cooperative Script learning model is a learning model in pairs and each individual in the pair summarizes the material that has been learned. With this model students are expected to learn in pairs and conclude their own material that has been determined. Then by itself is expected to improve student achievement. The purpose of this study was to determine the application of Cooperative Script learning models for fourth grade students of PAI subjects at SDN 009 Parat Teratak Air Hitam, Sentajo Raya District, Kuantan Singingi District. and 15 women and as an object are the application of the Cooperative Script learning model in improving the learning achievement of fourth grade students of PAI in Negeri 009 Trench Teratak Air Hitam, Sentajo Raya District, Kuantan Singingi Regency. With data collection techniques through observation, tests, interviews and documentation and data processing using percentage charts / graphs. The application of the Cooperative Script learning model for Grade IV students of PAI in 009 Teratak Air Hitam Trench Sentajo Raya District has been carried out well from each cycle, pre cycle 100%, Cycle I: 100%, Cycle II: 100%, and cycle III : also 100%. This is proven by 9 people who have not completed the pre-cycle, cycle I: 5 people who have not yet finished, cycle II: 2 people who have not yet finished and cycle III has all been completed (27 people). Kata Kunci : Model Pembelajaran Kooperative Script, prestasi belajar siswa